ISOLATION OF LIPID AND IDENTIFICATION OF FATTY ACID FROM THE TROPICAL MARINE MICROALGAE THALASSIOSIRA SP. CULTIVATED IN A 1.500 L OUTDOOR PHOTOBIOREACTOR - APRIANTO ( NIM : 10511057 ), FADLI
Oil productivity of the tropical marine microalgae Thalassiosira sp. cultivated in indoor photobioreactors of 237 mg L–1 d–1 has been reported previously. The purpose of the present research was to determine the oil productivity as well as to identify fatty acids content of lipid obtained from Thalasiosira sp. biomass produced in a 1,500-L outdoor photobioreactor. The outdoor biomass production of Thalassiosira sp. was carried out from initial starter cultures obtained by gradually seeding. Lipid was extracted from the biomass by the method of modified Bligh-Dyer, and the productivity of biomass and lipid were determined. Fatty acids content was identifed by GC-MS. The results showed that the average of Thalassiosira sp. cell density cultivated with an initial concentration of 8.77×105 cell/mL in a 1,500-L outdoor photobioreactor for 6 d was 3.06×106 cell/mL. The Thalassiosira sp. biomass obtained was 844 g, or equivalent to the biomass productivity of 93.8 mg L–1 d–1. The lipid productivity of Thalassiosira sp. obtained was 1.2 mg L–1 d–1. The fatty acid contents (and its relative abundance) of Thalassiosira sp. lipid identified by GC-MS were myristic acid (C14:0, 1.55%), pentadecanoic acid (C15:0, 0.37%), palmitoleic acid (C16:1n-9, 1.19%), palmitic acid (C16:0, 29.55%), linoleic acid (C18:2n- 6, 9.61%), elaidic acid (C18:1n-9t, 1.75%), oleic acid (C18:1n-9c, 46.56%), stearic acid(C18:0, 5.02%), arachidic acid (C20:0, 0.34%), and lignoceric acid (C24:0, 0.32%).